Functional Head Impulse Test in Professional Athletes: Sport-Specific Normative Values and Implication for Sport-Related Concussion - Romano, Fausto; Bertolini, Giovanni; Agostino, Daniel; Straumann, Dominik; Ramat, Stefano; Feddermann-Demont, Nina (Frontiers in Neurology, 2019)
Dizziness, slow visual tracking, or blurred vision following active head (or body) movements are among the most common symptoms reported following sport-related concussion, often related to concurrent dysfunctions of the vestibular system. In some cases, symptoms persist even if bedside and auxiliary standard vestibular tests are unremarkable. New functional tests have been developed in recent years to objectify neurological alterations that are not captured by standard tests. The functional head impulse test (fHIT) requires the patient to recognize an optotype that is briefly flashed during head rotations with various angular accelerations (2001-6000 deg/s2) and assesses the proportion if correct answers (pca). 268 active professional athletes (23.70±5.32y) from six different sports were tested using fHIT. Pca were analyzed both pooling head acceleration in the range of 2001-6000 deg/s2 and computing a single pca value for each 1000 deg/s2 bin in the range 2001-8000 deg/s2. No significant difference (p-value=0.159) was found between responses to head impulses in the plane of horizontal (pca: 0.977) and vertical semicircular canals (pca: 0.97). The sport practiced had a major effect on the outcome of the fHIT. Handball players achieved a better performance (p<0.001) than the whole athlete group, irrespective of the direction of head impulses. The pca achieved by athletes practicing snowboard, bob and skeleton were instead significantly below those of the whole athlete group (p<0.001) but only when vertical head impulses were tested. Overall, pca declined with increasing head acceleration. The decline was particularly evident in the range not included in the standard fHIT exam, i.e. 6001-8000 deg/s2 for horizontal and 5001-8000 deg/s2 for vertical head impulses. When vertical head impulses were tested, athletes practicing snowboard, bob and skeleton (non-ball sports) showed, beside the lower overall pca, also a steeper decline as a function of vertical head acceleration. The findings suggest that: 1) functional VOR testing can help understanding sport-specific VOR requirements; 2) the fHIT is able to detect and objectify subtle, sport-specific changes of functional VOR performance; 3) if sport-specific normative values are used, the fHIT test procedure needs to be optimized, starting from the highest acceleration to minimize the number of head impulses.